Jan T. Bonarski (1957–2016). Issue 2 (1st March 2016) - Chateigner, Daniel; Baudin, Thierry; Esling, Claude; Morawiec, Adam; Solas, Denis
Abstract : Obituary for Jan T. Bonarski. Abstract : Obituary for Jan T. Bonarski.